The knowledge, attitude and practice among primary health care nurse practitioners regarding oral health and oral HIV lesions in QE II and Roma health service areas in Maseru, Lesotho - Prithiviraj, Thamotharampillai Gerard (My University, 2012)
Although the nursing sector has not been spared the effects of human resource shortages and Human Immune-deficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) crisis in Lesotho, it still remains the backbone of the primary health care delivery. There is a well-established linkage between oral health and HIV/AIDS with many of the early symptoms of HIV manifesting in the oro-facial region. However, the lack of oral health personnel at primary health care levels in Lesotho makes Primary Health Care Nurse Practitioners (PHCNPs) often the first health care providers to consult, manage and refer patients with such oral lesions. Aim: To assess the “knowledge, attitude and practice” (KAP) of the PHCNPs regarding oral health and oral HIV lesions in Queen Elizabeth II (QE II) and Roma health service areas (HSA) of Maseru district in Lesotho. Objectives: To assess the demographic profile of PHCNPs in the target health facilities, their knowledge, attitude and practice regarding oral health and oral HIV lesions. Methods and Materials: The research was a descriptive cross-sectional survey. A convenience sample of 57 primary health care nurse practitioners (PHCNPs) from QE II and Roma health service areas were identified. During their monthly PHC meeting, a questionnaire was administered to assess the knowledge, attitude and practice regarding oral health and oral HIV lesions. The information gathered was both quantitative and qualitative. Data was entered and analysed using the SPSS statistical package. Results: The response rate was 87.7%. There was 100% consensus regarding the importance of oral health to the total well being of individuals. The majority of the PHCNPs recognised oral candidiasis (OC) (94.7%), bleeding gums (87.7%), herpes lesions (71.9%) and dental caries (75.4%). Lesions such as acute necrotizing ulcerative gingivitis (ANUG) (40.3%), angular cheilitis (AC) (56.1%) and apthous ulcerations (24.6%) were also recognised but to a lesser extent. The respondents associated OC (84%), herpes (61%), AC (54%), Oral Hairy Leukoplakia (OHL) (49%), Kaposi‟s‟ sarcoma (KS) (49%) with HIV/AIDS. OC was the most common lesion associated with HIV. Some lesions commonly seen in the clinics such as apthous ulceration and ANUG were not significantly associated with HIV (18% and 33%, respectively). The majority of PHCNPs (81%) indicated that they had knowledge about oral HIV lesions. Twenty nine 6 respondents (50.8 %) reported having received this knowledge through training institutions. Mass media (Radio (53%), TV (40%), and newspapers/magazines (49%)) was one of the major sources of information. Forty-four PHCNPs (77.2%) saw only Zero or one (0-1) HIV patients with oral lesions. Similarly, 15.8 % and 7% of the PHCNPs saw 11 to 20 and more than 20 (21+) HIV patients with oral lesions, respectively. The two thirds of the PHCNPs (67%) said they would not advise patients to seek care from Traditional Health Practitioners (THP) due to their lack of trust and confidence in the practices, knowledge and the patient management of the THPs. However, 16% of them reported that they would refer because they thought traditional medicine boosts the immune system. Only seven respondents (12.3%) routinely washed their hands with antiseptics. However, 44 of respondents (77.2 %) cleaned their instruments with bleach and disinfectants. The majority (89.5%) washed their hands with water and soap. Forty three respondents (75.4%) wore gloves during examination. Routine use of facemasks was limited to only 12 respondents (21.1 %). Ninety eight percent of the PHCNPs stated that they would like to learn to manage oral lesions at health centres. The majority (79%) of the respondents said that they would like to receive more training on the management of oral lesions through workshops. Conclusions: There was an observable correlation between PHCNPs self-assessment of oral health knowledge and the objective knowledge as assessed by ability to identify the oral lesions on a chart ( 2 –sided Fischer‟s test-0.000-0.261).This needs to be confirmed by undertaking a study with a larger sample size. OC was the most common lesion associated with HIV as reported by the PHCNPs. The majority of the participants (94.7%) identified OC and associated it (84%) with HIV infection. The finding indicated that with training and/or mentoring, PHCNPs are likely to confidently diagnose oral HIV lesions. PHCNPs showed a positive attitude towards learning more about the oral manifestations of HIV/AIDS. PHCNPs should be utilised more effectively in the diagnosis and management of HIV/AIDS.
M.P.H., Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: primary health care nurse practitioners (PHCNPs); oral mucosal lesions; oral HIV; AIDS